Potensi PET (Polyethylene Terephthalate) Sebagai Bahan Baku Ecological Brick - Brillyan Rahman; David Andrio; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The use of plastics and plastic-based goods is increasing with the development of technology, industry, and population. Increasing plastic demand automatically increases waste generation as well. PET is a type of plastic type 1. Brick is a building material that is still very important in construction work. In this study, we propose the use of PET waste and the potential of PET in minimizing PET waste in Indonesia. Our results show that ecological brick making products still meet the requirements of SNI 03-0349-1989, and eco-brick making has the potential to reduce PET waste in Indonesia. Keywords: ecological brick, plastics, polyethylene terephthalate